META ANALISIS EFEKTIVITAS MEDIA COUNTING BOX TERHADAP HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA - Chiorun Nisa Afidatus Zahro; Sri Hartatik; Dewi Widiana Rahayu; Pance Mariati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of using the Counting box media on elementary students' mathematics learning outcomes through a meta-analysis approach. The Counting box is a concrete learning tool that helps students visualize and understand basic arithmetic operations such as addition and subtraction more contextually. This study employed a literature review using a qualitative meta-synthesis approach on 12 scientific articles published between 2021 and 2025 that met the inclusion criteria. The findings indikyhcate that the use of Counting box consistently improves students' learning outcomes in cognitive, affective, and psychomotor domains. This media also enhances students’ learning motivation and active engagement in mathematics instruction. These results support the Counting box as an effective and applicable instructional medium at the elementary school level.